Magnesium alloy and preparation method thereof

By adding Sm, Zn and Mn elements to magnesium alloys to prepare nano-scale α-Mn particles and Mg3Sm phases, the problem of magnesium alloys having both strength and plasticity is solved, and low-cost industrial production of magnesium alloys is achieved.

CN120591634APending Publication Date: 2025-09-05GUANGDONG INST OF NEW MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510923478.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-04
Publication Date
2025-09-05

AI Technical Summary

Technical Problem

Existing magnesium alloys have difficulty in achieving both strength and plasticity, and are also relatively expensive.

Method used

By adding Sm, Zn and Mn elements to the magnesium alloy, the preparation method includes melting, casting, homogenization and extrusion, controlling the content and temperature conditions of each element, forming nano-scale α-Mn particles and Mg3Sm phase, and optimizing texture strength.

Benefits of technology

A low-cost magnesium alloy with both strength and plasticity was obtained, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120591634A_ABST
    Figure CN120591634A_ABST
Patent Text Reader

Abstract

The invention discloses a magnesium alloy and a preparation method thereof, and belongs to the technical field of magnesium alloy materials. The magnesium alloy comprises the following components in percentage by mass: more than 0% and less than or equal to 3% of Mn, 0.5%-1.5% of Sm, 0.7%-1% of Zn and the balance of Mg and inevitable impurities. The magnesium alloy has good plastic deformation capacity. The preparation method of the magnesium alloy comprises the following steps: adding pure zinc into molten pure magnesium, heating to melt the pure zinc, then adding an Mg-Mn intermediate alloy and an Mg-Sm intermediate alloy, and heating to melt each intermediate alloy to obtain a molten alloy; preparing the molten alloy into a cast ingot; and the cast ingot is subjected to homogenization and extrusion forming. The method is simple, easy to operate and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnesium alloys, and in particular to a magnesium alloy and a preparation method thereof. Background Art

[0002] Magnesium alloy is an alloy composed of magnesium and other elements. In the existing technology, elements such as Al, Ca, Y, and Gd are usually added to improve the mechanical properties and impact toughness of magnesium alloy. However, the magnesium alloy obtained by the above method often has difficulty in achieving both strength and plasticity, and the magnesium alloy has poor ability to resist deformation.

[0003] In view of this, the present invention is proposed. Summary of the Invention

[0004] The object of the present invention is to provide a magnesium alloy and a preparation method thereof to solve or improve the above technical problems.

[0005] The present invention can be implemented like this: In a first aspect, the present invention provides a magnesium alloy comprising, by mass percentage, >0% and ≤3% Mn, 0.5%-1.5% Sm, and 0.7%-1% Zn, with the remainder being Mg and unavoidable impurities.

[0006] In an optional embodiment, the magnesium alloy contains >0% and ≤1% of Mn, 0.8%-1.5% of Sm, and 0.7%-1% of Zn, with the balance being Mg and unavoidable impurities.

[0007] In an alternative embodiment, the magnesium alloy contains 1% of Mn, 1.5% of Sm, and 1% of Zn, with the balance being Mg and inevitable impurities.

[0008] In an optional embodiment, the magnesium alloy contains nano-scale α-Mn particles formed by solid solution of the Mn element; and / or the magnesium alloy contains a Mg3Sm phase.

[0009] In a second aspect, the present invention provides a method for preparing a magnesium alloy as described in any of the aforementioned embodiments, comprising the following steps: adding pure zinc to molten pure magnesium, heating to melt the pure zinc, then adding a Mg-Mn intermediate alloy and a Mg-Sm intermediate alloy, heating to melt the intermediate alloys to obtain a molten alloy; preparing the molten alloy into an ingot; and homogenizing and extruding the ingot.

[0010] In an optional embodiment, the pure magnesium alloy is melted at 705° C. to 715° C.; and / or, melting pure zinc at 725°C to 735°C; and / or, melting the master alloy at 735° C. to 745° C.

[0011] In an optional embodiment, preparing the molten alloy into an ingot includes: stirring the molten alloy at 685°C~695°C at a rotation speed of 380rpm~420rpm for 5min~15min, then heating it to 705°C~715°C, keeping it warm for 2min~8min, and casting it into an ingot in a mold.

[0012] In an optional embodiment, the homogenization is performed at 495° C. to 505° C. for 14 h to 18 h.

[0013] In an optional embodiment, before extrusion, the method further includes preheating the homogenized cast billet; The preheating temperature is 425℃~435℃, and the preheating time is 1h~3h.

[0014] In an optional embodiment, the extrusion temperature is 445° C. to 455° C., and the extrusion rate is 0.6 mm / min to 1 mm / min.

[0015] The beneficial effects of the present invention include: The present invention reduces the structural strength of magnesium alloys while also lowering their cost by adding Sm. The addition of Zn refines the grains and promotes the formation of a large amount of Mg3Sm phase, significantly enhancing both aging and precipitation strengthening. The addition of Mn refines the grains while also improving the deformation resistance and plasticity of the magnesium alloy. In other words, the present invention achieves a Mg-Sm-Zn-Mn wrought magnesium alloy that combines strength and plasticity with low cost through the coordinated use of Sm, Zn, and Mn.

[0016] The magnesium alloy preparation method is simple, easy to operate and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without paying any creative work.

[0018] Figure 1 A flow chart of the preparation of the magnesium alloy provided by the present invention; Figure 2 The scanning electron microscope images of the magnesium alloys prepared in Examples 1 to 3 are shown; Figure 3 for Figure 2 A magnified image of the marked area and the energy dispersion spectrum results of some marked points; Figure 4 BF image, HAADF-STEM image and EDX mapping image of the magnesium alloy prepared in Example 1; Figure 5 These are the high-angle annular dark field scanning transmission electron microscope image and EDS image of the magnesium alloy prepared in Example 1. DETAILED DESCRIPTION To make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer are used. Where the manufacturer of the reagents or instruments is not specified, all are conventional products that can be purchased commercially.

[0019] The magnesium alloy and its preparation method provided by the present invention are described below.

[0020] The present invention provides a magnesium alloy. Calculated by mass percentage, the magnesium alloy contains Mn (>0% and ≤3%), Sm (0.5%-1.5%), and Zn (0.7%-1%), with the remainder being Mg and unavoidable impurities.

[0021] The present invention reduces the structural strength of magnesium alloys while also lowering their cost by adding Sm. The addition of Zn refines the grains and promotes the formation of a large amount of Mg3Sm phase, significantly enhancing both aging and precipitation strengthening. The addition of Mn refines the grains while also improving the deformation resistance and plasticity of the magnesium alloy. In other words, the present invention achieves a Mg-Sm-Zn-Mn wrought magnesium alloy that combines strength and plasticity with low cost through the coordinated use of Sm, Zn, and Mn.

[0022] In some optional embodiments, the amount of Mn contained in the magnesium alloy may be 0.1%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, or 3.0%, or may be other values ​​within the range of >0% and ≤3%. If the Mn content in the magnesium alloy is less than 0.1%, the strain hardening exponent of the magnesium alloy will be small, making it prone to deformation. If the Mn content in the magnesium alloy is greater than 3%, the excess Mn element will segregate, hindering dislocation movement and reducing the plasticity of the material.

[0023] The amount of Sm contained in the magnesium alloy can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, or 1.5%, or other values ​​within the range of 0.5% to 1.5%. If the Sm content in the magnesium alloy is less than 0.5%, the texture strength of the magnesium alloy material is too high, resulting in a low elongation of the magnesium alloy. If the Sm content in the magnesium alloy is higher than 1.5%, excessive second phases are generated, reducing the elongation of the magnesium alloy.

[0024] The amount of Zn contained in the magnesium alloy can be 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, or 1%, or other values ​​within the range of 0.7% to 1%. If the Zn content in the magnesium alloy is less than 0.7%, the strengthening effect is poor; if the Zn content in the magnesium alloy is greater than 1%, the ductility of the magnesium alloy decreases. This is due to the following reasons: During tensile deformation, the coarse grains of the Zn-containing Mg-Sm alloy promote the nucleation of randomly oriented recrystallized grains through the PSN effect. At the same time, a large number of coarse particles easily become sites for crack initiation, resulting in a decrease in elongation.

[0025] In some preferred embodiments, the magnesium alloy contains >0% and ≤1% Mn, 0.8%-1.5% Sm, and 0.7%-1% Zn, with the balance being Mg and unavoidable impurities.

[0026] In some more preferred embodiments, the magnesium alloy contains 1% Mn, 1.5% Sm, and 1% Zn, with the balance being Mg and inevitable impurities.

[0027] The magnesium alloy provided by the present invention contains nanoscale α-Mn particles formed by the solid solution of the element Mn. These nanoscale α-Mn particles restrict grain boundary movement through the Smith-Zener pinning effect, thereby preventing the growth of DRXed grains, resulting in grain refinement and texture weakening. Furthermore, the magnesium alloy provided by the present invention also contains a Mg3Sm phase to enhance aging and precipitation strengthening.

[0028] Accordingly, the present invention also provides a method for preparing the above magnesium alloy, such as Figure 1 As shown, the process includes the following steps: adding pure zinc to molten pure magnesium, heating to melt the pure zinc, then adding Mg-Mn master alloy and Mg-Sm master alloy, heating to melt the master alloys to obtain molten alloy; preparing the molten alloy into an ingot; and homogenizing and extruding the ingot.

[0029] The above preparation and melting processes are all carried out in a resistance furnace by induction melting under the protection of a protective atmosphere (such as argon).

[0030] The purity of Mg in pure magnesium is not less than 99.96 wt%, and the purity of Zn in pure zinc is not less than 99.96 wt%. The Mg-Mn master alloy may be, for example, a Mg-10 wt% Mn alloy (which can be understood as containing 10 wt% Mn in the Mg-10 wt% Mn alloy), and the Mg-Sm master alloy may be, for example, a Mg-20 wt% Sm alloy (which can be understood as containing 20 wt% Mn in the Mg-20 wt% Sm alloy).

[0031] In some optional embodiments, pure magnesium may be melted at 705° C. to 715° C. (eg, 705° C., 708° C., 710° C., 712° C., or 715° C.).

[0032] In some optional embodiments, pure zinc may be melted at 725° C. to 735° C. (eg, 725° C., 728° C., 730° C., 732° C., or 735° C.).

[0033] In some optional embodiments, the master alloy may be melted at a temperature between 735° C. and 745° C. (eg, 735° C., 738° C., 740° C., 742° C., or 745° C.).

[0034] In some optional embodiments, preparing the molten alloy into an ingot includes: stirring the molten alloy at a temperature of 685°C to 695°C (such as 685°C, 688°C, 690°C, 692°C or 695°C, etc.) at a speed of 380rpm to 420rpm (such as 380rpm, 400rpm or 420rpm, etc.) for 5min to 15min (such as 5min, 10min or 15min, etc.), then heating to 705°C to 715°C (705°C, 708°C, 710°C, 712°C or 715°C, etc.), keeping warm for 2min to 8min (such as 2min, 5min or 8min, etc.), and casting the molten alloy into an ingot in a mold.

[0035] In some optional embodiments, homogenization is performed at 495°C to 505°C (such as 495°C, 498°C, 500°C, 502°C or 505°C, etc.) for 14h to 18h (such as 14h, 15h, 16h, 17h or 18h, etc.).

[0036] In some optional embodiments, the homogenized cast billet is preheated before extrusion. The preheating temperature may be 425°C to 435°C (e.g., 425°C, 428°C, 430°C, 432°C, or 435°C), and the preheating time may be 1 hour to 3 hours (e.g., 1 hour, 1.5 hours, 2 hours, 2.5 hours, or 3 hours).

[0037] In some optional embodiments, the extrusion temperature can be 445°C~455°C (445°C, 448°C, 450°C, 452°C or 455°C, etc.), and the extrusion rate can be 0.6mm / min~1mm / min (such as 0.6mm / min, 0.7mm / min, 0.8mm / min, 0.9mm / min or 1mm / min, etc.).

[0038] Under the above-mentioned homogenization, preheating and hot extrusion conditions, the Mn element can be effectively dissolved into nano-scale α-Mn particles.

[0039] It should be emphasized that the solid solubility of manganese in the Mg matrix increases with increasing temperature. At temperatures of approximately 550°C, 650°C, and 705°C, the solid solubility of manganese is approximately 1%, 2%, and 2.5%, respectively. In the present invention, maintaining the melting temperature above 550°C effectively allows the manganese element to be fully dissolved into the Mg alloy. Setting the melting temperature of pure zinc to 725°C–735°C further ensures complete melting of the magnesium. During ingot preparation, stirring the alloy at 685°C–695°C for a period of time can make the molten alloy more homogeneous; heating the alloy after stirring can increase the solubility of manganese in magnesium. Controlling the homogenization temperature and time between 495°C and 505°C for 14–18 hours ensures sufficient solid solubility of manganese while preventing grain growth due to excessively high temperatures, thereby producing nano-sized α-Mn particles. Preheating the alloy prior to extrusion facilitates extrusion, promotes dynamic recrystallization, and improves elongation. The ingot is hot extruded with the extrusion temperature set at 445℃~455℃, which can ensure the smooth extrusion of the magnesium alloy sheet while preventing grain growth during the extrusion deformation process due to excessively high temperature. It can also promote dynamic recrystallization of the magnesium alloy during the deformation process and refine the grains.

[0040] The features and performance of the present invention are further described in detail below with reference to the embodiments.

[0041] Example 1 This embodiment provides a magnesium alloy containing 1% of Mn, 1.5% of Sm, and 1% of Zn, with the remainder being Mg and unavoidable impurities.

[0042] The preparation method of the magnesium alloy comprises: S1: Melting.

[0043] Pure magnesium (>99.96wt%) is placed in a crucible and the resistance furnace temperature is raised to 710°C until the pure magnesium is completely melted. Pure zinc (>99.96wt%) is then added to the melt and the melt temperature is raised to 730°C until the pure zinc is melted. Finally, the master alloys Mg-10wt%Mn and Mg-20wt%Sm are added to the melt and the temperature is maintained at 735°C-745°C for approximately 10 minutes to obtain a molten alloy.

[0044] S2: Casting.

[0045] The molten alloy was stirred at 690° C. at a stirring speed of 400 rpm for 10 minutes; then, the temperature was raised to 710° C. and maintained for 5 minutes, and then the molten alloy was poured into a mold to obtain an ingot.

[0046] S3: Homogenized.

[0047] The ingot was processed into a cylindrical billet with a diameter of 100 mm and a height of 80 mm, and homogenized at 500 °C for 16 h to obtain a cast billet.

[0048] S4: Squeeze.

[0049] The as-cast billet was preheated at 430°C for 2 h and then extruded into a 3 mm thick plate at a temperature of 450°C and an extrusion rate of 0.8 mm / min.

[0050] The maximum texture strength of the extruded magnesium alloy sheet is 3.11 mrd; the transverse yield strength is 122.8 MPa, the elongation is 40.1%; the longitudinal yield strength is 147.7 MPa, and the elongation is 21.4%.

[0051] Example 2 The difference between this embodiment and embodiment 1 is that the magnesium alloy contains 1% of Mn, 1.0% of Sm and 0.8% of Zn, with the remainder being Mg and unavoidable impurities.

[0052] The maximum texture strength of the extruded magnesium alloy sheet is 3.89 mrd; the transverse yield strength is 108.65 MPa, and the elongation is 31.42%; the longitudinal yield strength is 142.68 MPa, and the elongation is 22.63%.

[0053] Example 3 The difference between this embodiment and embodiment 1 is that the magnesium alloy contains 0.5% of Mn, 0.8% of Sm and 0.7% of Zn, with the remainder being Mg and unavoidable impurities.

[0054] The maximum texture strength of the extruded magnesium alloy sheet is 6.96 mrd; the transverse yield strength is 108.36 MPa, the elongation is 39.06%; the longitudinal yield strength is 130.33, and the elongation is 22.31%.

[0055] Example 4 The difference between this embodiment and embodiment 1 is that the magnesium alloy contains 3% of Mn, 0.5% of Sm and 0.7% of Zn, with the remainder being Mg and unavoidable impurities.

[0056] The maximum texture strength of the extruded magnesium alloy sheet is 22.79 mrd; the transverse yield strength is 120.36 MPa, the elongation is 8.62%; the longitudinal yield strength is 132.59 MPa, and the elongation is 6.50%.

[0057] Example 5 The difference between this embodiment and embodiment 1 is that the preparation parameters are different, as follows: The preparation method of the magnesium alloy comprises: S1: Melting.

[0058] Pure magnesium (>99.96wt%) is placed in a crucible and the resistance furnace temperature is raised to 705°C until the pure magnesium is completely melted. Pure zinc (>99.96wt%) is then added to the melt and the melt temperature is raised to 725°C until the pure zinc is melted. Finally, the master alloys Mg-10wt%Mn and Mg-20wt%Sm are added to the melt and the temperature is maintained at 735°C-745°C for approximately 15 minutes to obtain a molten alloy.

[0059] S2: Casting.

[0060] The molten alloy was stirred at 685° C. at a stirring speed of 420 rpm for 15 minutes; then, the temperature was raised to 705° C. and maintained for 8 minutes, and then the molten alloy was poured into a mold to obtain an ingot.

[0061] S3: Homogenized.

[0062] The ingot was processed into a cylindrical billet with a diameter of 100 mm and a height of 80 mm, and homogenized at 495 °C for 18 h to obtain a cast billet.

[0063] S4: Squeeze.

[0064] The as-cast billet was preheated at 425°C for 3 h and then extruded into 3 mm thick plates at a temperature of 445°C and an extrusion rate of 0.6 mm / min.

[0065] The maximum texture strength of the extruded magnesium alloy sheet is 4.63 mrd; the transverse yield strength is 101.52 MPa, and the elongation is 32.96%; the longitudinal yield strength is 140.29%, and the elongation is 23.37%.

[0066] Example 6 The difference between this embodiment and embodiment 1 is that the preparation parameters are different, as follows: The preparation method of the magnesium alloy comprises: S1: Melting.

[0067] Pure magnesium (>99.96wt%) is placed in a crucible and the resistance furnace temperature is raised to 715°C until the pure magnesium is completely melted. Pure zinc (>99.96wt%) is then added to the melt and the melt temperature is raised to 735°C until the pure zinc is melted. Finally, the master alloys Mg-10wt%Mn and Mg-20wt%Sm are added to the melt and the temperature is maintained at 735°C-745°C for approximately 5 minutes to obtain a molten alloy.

[0068] S2: Casting.

[0069] The molten alloy was stirred at 695° C. at a stirring speed of 380 rpm for 5 min; then, the temperature was raised to 715° C. and maintained for 2 min, and then the molten alloy was poured into a mold to obtain an ingot.

[0070] S3: Homogenized.

[0071] The ingot was processed into a cylindrical billet with a diameter of 100 mm and a height of 80 mm, and homogenized at 505 °C for 14 h to obtain a cast billet.

[0072] S4: Squeeze.

[0073] The as-cast billet was preheated at 435°C for 1 h and then extruded into 3 mm thick plates at a temperature of 455°C and an extrusion rate of 1 mm / min.

[0074] The maximum texture strength of the extruded magnesium alloy sheet is 8.37 mrd; the transverse yield strength is 116.35 MPa, and the elongation is 25.31%; the longitudinal yield strength is 148.93%, and the elongation is 19.66%.

[0075] Comparative Example 1 The difference between this comparative example and Example 1 is that the Mn content in the magnesium alloy is increased to 3.5 wt %.

[0076] Comparative Example 2 The difference between this comparative example and Example 1 is that the Sm content in the magnesium alloy is reduced to 0.2 wt %.

[0077] Comparative Example 3 The difference between this comparative example and Example 1 is that the Sm content in the magnesium alloy is increased to 2 wt %.

[0078] Comparative Example 4 The difference between this comparative example and Example 1 is that the Zn content in the magnesium alloy is reduced to 0.5 wt %.

[0079] Comparative Example 5 The difference between this comparative example and Example 1 is that the Zn content in the magnesium alloy is increased to 1.2 wt %.

[0080] Comparative Example 6 The difference between this comparative example and Example 1 is that La is used in an equal amount to replace Sm.

[0081] Comparative Example 7 The difference between this comparative example and Example 1 is that an equal amount of Ce is used to replace Sm.

[0082] Comparative Example 8 The difference between this comparative example and Example 1 is that an equal amount of Ca is used to replace Mn.

[0083] Comparative Example 9 The difference between this comparative example and Example 1 is that the melting temperature of pure zinc is also 710°C.

[0084] Comparative Example 10 The difference between this comparative example and Example 1 is that in S2, the molten alloy was stirred at 690° C. at a stirring speed of 400 rpm for 10 minutes and then directly poured into the mold.

[0085] Comparative Example 11 The difference between this comparative example and Example 1 is that in S2, the temperature of the molten alloy is directly raised to 710° C., maintained for 5 minutes, and then poured into the mold.

[0086] Comparative Example 12 The difference between this comparative example and Example 1 is that in S3, the homogenization temperature is 490°C.

[0087] Comparative Example 13 The difference between this comparative example and Example 1 is that in S3, the homogenization temperature is 510°C.

[0088] Comparative Example 14 The difference between this comparative example and Example 1 is that in S4, the as-cast billet is not preheated, but is directly extruded at a temperature of 450° C. and an extrusion rate of 0.8 mm / min.

[0089] Comparative Example 15 The difference between this comparative example and Example 1 is that in S4, the extrusion temperature is 460°C.

[0090] Test Example 1 The magnesium alloys prepared in Examples 1 to 3 were observed by scanning electron microscopy. Figure 2 and Figure 3 As shown, (a) corresponds to the SEM image of the magnesium alloy prepared in Example 3, (b) corresponds to the SEM image of the magnesium alloy prepared in Example 2, and (c) corresponds to the SEM image of the magnesium alloy prepared in Example 1.

[0091] Depend on Figure 2 It can be seen that the magnesium alloys prepared in each of the above examples all exhibit an extrusion band along the extrusion direction (ED), and the Mg3Sm phase within the magnesium alloy is elongated and distributed along the extrusion direction. Furthermore, as the Mn content increases, not only does the content of the precipitated phase increase, but its distribution also becomes more uniform.

[0092] Figure 3 (a) is Figure 2 Magnified image of the marked area in (a). Figure 3 (b) is Figure 2 (b) Enlarged view of the marked area. Figure 3 (c) is Figure 2 (c) Enlarged view of the marked area. Figure 3 (d) is Figure 3 Energy dispersive spectroscopy (EDS) results in (a) to (c). Figure 3 Result 1 in (d) corresponds to Figure 3 Point 1 in (a); Figure 3 Results 2 and 3 in (d) correspond to Figure 3 Points 2 and 3 in (b); Figure 3 The results 4 and 5 in (d) correspond to Figure 3 Points 4 and 5 in (c).

[0093] Figure 4 (a) and Figure 4 (b) is the BF image and HAADF-STEM image of Example 1; Figure 4 (c) to (f) are EDX mapping images of Example 1, corresponding to the four elements Mg, Mn, Sm and Zn, respectively.

[0094] Depend on Figure 4 It can be seen that many black block-shaped and spherical particles with an average size of about 300 nm are observed in the magnesium alloy, and a large number of fine black particles with an average size of about 60 nm are uniformly distributed in the α-Mg matrix.

[0095] Figure 5 The high-angle annular dark field scanning projection electron microscope image and EDS image of Example 1 are shown; wherein, Figure 5 (a) is a TEM micrograph of the precipitated phase α-Mn. Figure 5 (b) is the SAED photo of the precipitated phase α-Mn. Figure 5 (c) EDS point scanning results of the precipitated phase α-Mn. Figure 5 (d) is a TEM micrograph of the precipitated phase Mg3Sm. Figure 5 (e) is the SAED photo of the precipitated phase Mg3Sm. Figure 5 (f) in the middle is the EDS point scanning result of the precipitated phase Mg3Sm.

[0096] Depend on Figure 4 and Figure 5 It can be seen that the second phase in the magnesium alloy prepared in Example 1 is the Mg3Sm phase, and the white diffuse phase is composed of α-Mn particles.

[0097] Test Example 2 Taking Example 1 as an example, control groups 1 and 2 were set. The difference between Control Group 1 and Example 1 was that the Mn content in the magnesium alloy was 0; the difference between Control Group 2 and Example 1 was that the Mn content in the magnesium alloy was 0.5 wt%.

[0098] The magnesium alloy sheets obtained in Example 1 and Controls 1-2 were tested for yield strength, ultimate tensile strength, elongation, and strain hardening index. Testing directions included the transverse direction, the 45° oblique direction, and the longitudinal direction. Yield strength, ultimate tensile strength, elongation, and strain hardening index were measured in accordance with GB / T 228.1, as well as in accordance with GB / T 228.1. The results are shown in Table 1.

[0099] Table 1 Test results

[0100] The average value of each group = (transverse strain hardening index + longitudinal strain hardening index + 2 × oblique strain hardening index) / 4.

[0101] As can be seen from Table 1, the strain hardening exponent decreases with increasing Mn content. The larger the strain hardening exponent value, the stronger the plate's ability to resist instability and thinning, and the less likely it is to deform. The smaller the strain hardening exponent value, the weaker the plate's resistance to instability and thinning, and the more susceptible it is to deformation.

[0102] The magnesium alloy plates obtained from the control group 2 and Example 1 have better deformation resistance and plasticity than the magnesium alloy plate obtained from the control group 1.

[0103] Test Example 2 The magnesium alloy sheets obtained in Comparative Examples 1 to 15 were tested according to the method of Test Example 1, and the results are shown in Table 2. The data in Table 2 are average values ​​of the transverse, oblique, and longitudinal directions.

[0104] Table 2 Test results

[0105] It can be seen from Table 2 that the magnesium alloy sheet prepared in the embodiment of the present invention has better mechanical strength and plasticity than the magnesium alloy sheet prepared in the comparative example.

[0106] By comparing Example 1 with Comparative Examples 1 to 5, it can be seen that when the content of Mn, Sm or Zn in the magnesium alloy is not properly set, it will cause an imbalance between strength and plasticity, and it is difficult to obtain a magnesium alloy with both good mechanical strength and plasticity.

[0107] By comparing Example 1 with Comparative Examples 6 to 8, it can be seen that when Mn or Sm in the magnesium alloy is replaced by other elements, the plasticity of the alloy plate decreases, and the strength is not enhanced, making it difficult to obtain a magnesium alloy with both good mechanical strength and plasticity.

[0108] By comparing Example 1 with Comparative Examples 10 to 15, it can be seen that when the preparation method or preparation conditions of the magnesium alloy are changed, the strength of the alloy plate will decrease, and it is difficult to obtain a magnesium alloy with both good mechanical strength and plasticity.

[0109] In summary, the present invention provides a Mg-Sm-Zn-Mn wrought magnesium alloy that has both strength and plasticity and is low-cost. The preparation method of the magnesium alloy is simple and suitable for industrial production.

[0110] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.

Claims

1. A magnesium alloy, characterized in that: Calculated by mass percentage, the magnesium alloy contains Mn (>0% and ≤3%), Sm (0.5%-1.5%), and Zn (0.7%-1%), with the remainder being Mg and unavoidable impurities.

2. The magnesium alloy according to claim 1, wherein The magnesium alloy contains Mn (>0% and ≤1%), Sm (0.8%-1.5%), and Zn (0.7%-1%), with the remainder being Mg and unavoidable impurities.

3. The magnesium alloy according to claim 2, characterized in that The magnesium alloy contains 1% of Mn, 1.5% of Sm, and 1% of Zn, with the remainder being Mg and inevitable impurities.

4. The magnesium alloy according to any one of claims 1 to 3, characterized in that The magnesium alloy contains nano-scale α-Mn particles formed by solid solution of Mn element; and / or the magnesium alloy contains Mg3Sm phase.

5. A method for preparing a magnesium alloy according to any one of claims 1 to 4, characterized in that: The following steps are involved: Pure zinc is added to the molten pure magnesium, and the mixture is heated to melt the pure zinc. Subsequently, a Mg-Mn master alloy and a Mg-Sm master alloy are added, and the master alloys are heated to melt the master alloys to obtain a molten alloy. The molten alloy is prepared into an ingot. The ingot is homogenized and extruded.

6. The preparation method according to claim 5, characterized in that Melting the pure magnesium at 705° C. to 715° C. and / or, melting the pure zinc at 725° C. to 735° C.; and / or, melting the master alloy at 735° C. to 745° C.

7. The preparation method according to claim 5, characterized in that The method of preparing the molten alloy into an ingot comprises: stirring the molten alloy at 685° C. to 695° C. at a rotation speed of 380 rpm to 420 rpm for 5 to 15 minutes, then heating the molten alloy to 705 to 715° C., keeping the temperature for 2 to 8 minutes, and casting the ingot into a mold.

8. The preparation method according to claim 5, characterized in that Homogenize at 495°C~505°C for 14h~18h.

9. The preparation method according to claim 5, characterized in that Before extrusion, the homogenized cast billet is preheated; The preheating temperature is 425℃~435℃, and the preheating time is 1h~3h.

10. The preparation method according to claim 5, characterized in that The extrusion temperature is 445°C~455°C, and the extrusion rate is 0.6mm / min~1mm / min.